Atividade antimicrobiana de extratos de Himatanthus articulatus (Vahl) Wood. (sucuba) - Costa, Bianca Jorge Sequeira (2006)
The use medicinal plants in the state of Roraima - Brazil is a very frequent and widespread therapeutical practice in the local community. In this work, methanol, hexane and ethyl acetate extracts were prepared using leaves, bark, stems and interbark of Himatanthus articulatus (Vahl) Wood., a characteristic species os Roraima`s savannah (lavrado), from the northern Brazilian Amazon. All the extracts were tested against ATCC and clinic strains of bacteria Staphylococcus aureus, Bacilus subtilis and Escherichia coli, as well as against the yeast Candida albicans. The results indicated that only extracts of methanol of some parts of this plant, beside the harvested latex of this plant and the commercial latex demonstrated antimicrobial action hindering the growth of bacteria.